The Effect of Pseudoexfoliation and Pseudoexfoliation Induced Dry Eye on Central Corneal Thickness. (3rd March 2016) - Akdemir, M. Orcun; Kirgiz, Ahmet; Ayar, Orhan; Kaldirim, Havva; Mert, Metin; Cabuk, Kubra Serefoglu; Taskapili, Muhittin
ABSTRACT: Purpose/aim of the study : The aim of this study is to investigate the effect of pseudoexfoliation (PEX) and PEX-induced dry eye on central corneal thickness (CCT). Materials and methods : This cross-sectional study consists of total 270 eyes of 135 patients (67 females, 68 males) in total. After excluding the PEX (−) 32 eyes with PEX in the other eye, totally 130 eyes in PEX (−) group and 108 eyes in the PEX (+) group were included in the study. The PEX (+) group was regrouped as PEX syndrome (80 eyes of 50 patients) and PEX glaucoma (28 eyes of 20 patients). Results : In the PEX (−) group, the mean Schirmer test result was 12 ± 4 mm (4–25 mm), in the PEX syndrome group 10 ± 4 mm (4–22 mm), in the PEX glaucoma group 9 ± 3 mm (4–15 mm). The difference among the PEX (−) group, the PEX syndrome and the PEX glaucoma groups was statistically significant ( p < 0.001, p < 0.001, respectively). In the PEX (−) group, the mean tear break up time test result was 11 ± 2 s (5–16 s), in the PEX syndrome group 8 ± 3 (3–16 s), in the PEX glaucoma group 8 ± 3 s (5–15 s). Mean CCT result was 544 µm in the PEX (−), 521 µm in the PEX syndrome group and 533 µm in the PEX glaucoma group. The difference among the PEX (−) group, the PEX syndrome and the PEX glaucoma groups was significant ( p < 0.001, p = 0.030, respectively). There was a significant (+) correlation between intraocular pressure and CCT in the eyes with PEX ( r = 0.307, p = 0.001). However, there was no statistically significant correlation between CCT, Schirmer and tear break up time tests in the eyes with PEX. Conclusions : PEX material can cause decrease in tear film secretion and disturb tear film stability. There is no effect of PEX-induced dry eye on CCT. Lower CCT values in the eyes with PEX material may be a result of decrease in corneal stromal cell density. Moreover, higher CCT values may be because of decreased endothelial cells in PEX glaucoma patients.